2012
DOI: 10.1111/j.1574-695x.2012.00958.x
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureusisolates belonging to different multilocus sequence types present specific virulence gene profiles

Abstract: To characterize 73 Staphylococcus aureus isolates from infections in an orthopedic hospital in Rio de Janeiro, we investigated the SCCmec types, the clonality by pulsed field gel electrophoresis and multilocus sequence typing, and the presence of virulence genes. Twenty‐eight (38.3%) methicillin‐resistant (16 SCCmec type IV and 12 type III) isolates were detected. Most (83.5%) of the isolates were included in five lineages: sequence type (ST) 239 (SCCmecIII), 1, 5, 30, and 1462 (SCCmecIV and/or methicillin‐sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
29
2
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 22 publications
6
29
2
2
Order By: Relevance
“…Although this study involves only one Brazilian hospital, the results reflect the decline in the prevalence of the BEC lineage and its replacement by other international clones, notably CC5 [3]. However, unlike other studies, we have identified a significant aggravating factor of clonal expansion of CC5 strains resistant to tigecycline but markedly less so to daptomycin.…”
contrasting
confidence: 56%
“…Although this study involves only one Brazilian hospital, the results reflect the decline in the prevalence of the BEC lineage and its replacement by other international clones, notably CC5 [3]. However, unlike other studies, we have identified a significant aggravating factor of clonal expansion of CC5 strains resistant to tigecycline but markedly less so to daptomycin.…”
contrasting
confidence: 56%
“…This lineage carrier of PVL genes had already been reported in Argentina (Egea et al, 2014;Fernandez et al, 2012) and in Brazil (Cavalcante et al, 2015;Caboclo et al, 2013;Schuenck et al, 2012). Moreover, in the present study, a VISA isolate belonging to USA1100/ST30 was identified, indicating the relevance of this lineage among the PVL-positive MRSA isolates.…”
mentioning
confidence: 49%
“…The bbp virulence gene, whose presence could be associated to osteomyelitis and arthritis (Tristan et al, 2003) had been related to the ST30 S. aureus lineage found in an orthopedic hospital (Schuenck et al, 2012). Here, we also found a correlation between the ST30 and the bbp gene, suggesting that this gene could be a possible marker of this lineage.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Em adição, tem sido observado em todo mundo, assim como no Brasil, a emergência de clones de MRSA que se apresentam sensíveis a vários antimicrobianos não betalactâmicos, em especial sulfametoxazoltrimetoprim (MATOS et al, 2014;MIRANDA et al, 2007;SCHUENCK et al, 2012;TRINDADE et al, 2005). Estas observações concordam com as realizadas no presente estudo, uma vez que a sensibilidade a sulfametoxazol-trimetoprim e gentamicina diminuíram 32 e 41%, de 2002 a 2011, respectivamente.…”
Section: Discussionunclassified